Back from the edge, a de-centred approach to ancient graffiti in Brazilian research - Feitosa, Lourdes; Garraffoni, Renata; Funari, Pedro Paulo (Huarte de San Juan. Geografía e Historia, 2024)
The paper starts with the trajectory of ancient graffiti study since the 19th century. This study was well inserted in the scholarly context, paying particular attention to the differences of language use in relation to standard learned Latin (or Greek). In the 20th century, beyond scholarship, there was an overwhelming normative and historical perception that graffiti represented most of all unlearned people, those who were unable to have access to learned culture. This improved the knowledge about graffiti, but it continued to focus on distance from the rule. In the late 20th century there was a growing critical approach, considering that graffiti may produce evidence about people’s daily lives. In this context, the edge has been able to produce a plethora of innovative interpretation. Brazil produced a critical approach, centring on a couple of subjects: popular culture and female agency. Popular culture means highlighting the originality of ordinary people culture. Then, within this approach, female agency. The authors then discuss some graffiti, enabling to discuss popular culture and female agency. The paper concludes by stressing how graffiti may be a way of promoting life, fostering living together, against hatred and destruction.